Pengaruh Model Pembelajaran Case Based Learning Terhadap Kemampuan Menulis Teks Berita Siswa Kelas XI SMK Swasta YWKA Medan Tahun Pembelajaran 2023/2024 - Sihombing, Reggia Margaretha (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
The aim of this research is to examine the impact of the Case Based Learning model on the news text writing skills of XI grade students at SMK Swasta YWKA Medan during the academic year 2023/2024. This study employed a quasi-experimental method utilizing a one-group pre-test post-test design, without a comparison group. The findings of the research revealed that prior to the implementation of the Case Based Learning model, the average news text writing ability of XI grade students at SMK Swasta YWKA Medan during the academic year 2023/2024 was rated as poor, with a mean score of 48.39. However, after the utilization of the Case Based Learning model, the average news text writing ability significantly improved to 77.47, categorized as good. Therefore, it can be concluded that the Case Based Learning model has a significant influence on enhancing the news text writing skills of XI grade students at SMK Swasta YWKA Medan during the academic year 2023/2024.